Implantasi Drug-eluting Stentatas Indikasi Off-label: Pengalaman dan Luaran Klinis di Pusat Jantung Nasional Harapan Kita - David D Ariwibowo; Daniel Tobing; Sunanto Ng; Muhammad Munawar; Sunarya A Soerianata (Jurnal Kardiologi Indonesia, 2008)
Background. Food and Drug Administration (FDA) of Unites States set the indication of drug-eluting stent (DES) on the product label (on-label indication). In the clinical practice, many patients received DES implantation outside the indication (off-label indication). Several “real-world” register showed off-label implantation reach prevalence of 50-60% with wide-ranging clinical outcomes.Objectives. To report the frequency, procedural complications, stent thrombosis (ST) and major cardiovascular events (MACE) of DES implantation with off-label indication in the National Cardiac Center Harapan Kita.Methods. This retrospective cohort study included patients who underwent coronary intervention with one or more DES (sirolimus or paclitaxel) implantation at 2006. Subjects were grouped into on-label and off-label indication. Subjects were followed-up until mid 2008.Results. 196(59%) of total patients who received DES implantation in 2006 in PJNHK are on off-label indications. The most frequent off-label indication was long-lesion intervention. There were more patients with previous myocardial infarction, PCI and CABG in off-label group. No significant difference of procedural complication rates between on-label and off-label group (2.2% vs. 2.6%, P =0.57). There was no significant difference of stent thrombosis rate. There was higher incident of MACE in off-label than on-labelgroup (17.9% vs. 8.6%, P =0.03). This difference was most contributed by incident of cardiac death. The adjusted hazard ratio of off-label was 1.7 (95% CI 0.8 – 3.6; P = 0.16); with several confounding factors including previous cerebrovascular disease, creatinine clearance <60 mL/min, non-elective PCI and double antiplatelet cessation. Conclusion. Off-label indication was quite frequent but has non-significant difference of TVR and ST rate compared to on-label indication. There was higher incident of MACE in off-label group, but this may be influenced by several clinical confounders.